2016
DOI: 10.1016/j.jcf.2016.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Sino nasal inhalation of isotonic versus hypertonic saline (6.0%) in CF patients with chronic rhinosinusitis — Results of a multicenter, prospective, randomized, double-blind, controlled trial

Abstract: Sinonasal inhalation with NaCl 6.0% did not lead to superior results vs. NaCl 0.9%, whereas dornase alfa had been significantly more effective than NaCl 0.9%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 29 publications
0
32
0
2
Order By: Relevance
“…Hypertonic saline causes reduced mucus viscoelasticity, improved mucociliary clearance and decongestion secondary to dissolution of mucus ionic bonds and osmosis, which allows rehydration of airway secretions. 64,65 In non-CF patients with CRS, a recent Cochrane review concluded that there is some benefit in disease-specific QOL with use of daily, large-volume (150mL), mildly hypertonic (2%) nasal saline irrigation in comparison to placebo. 66 However, recently published data from a multicenter, double-blind, randomized controlled trial found that sinonasal inhalation with hypertonic saline (NaCl 6.0%) applied with vibrating aerosols was not superior to isotonic (NaCl 0.9%) nasal saline irrigation in patients with CF-related CRS.…”
Section: Medical Management Of Cf-related Crsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypertonic saline causes reduced mucus viscoelasticity, improved mucociliary clearance and decongestion secondary to dissolution of mucus ionic bonds and osmosis, which allows rehydration of airway secretions. 64,65 In non-CF patients with CRS, a recent Cochrane review concluded that there is some benefit in disease-specific QOL with use of daily, large-volume (150mL), mildly hypertonic (2%) nasal saline irrigation in comparison to placebo. 66 However, recently published data from a multicenter, double-blind, randomized controlled trial found that sinonasal inhalation with hypertonic saline (NaCl 6.0%) applied with vibrating aerosols was not superior to isotonic (NaCl 0.9%) nasal saline irrigation in patients with CF-related CRS.…”
Section: Medical Management Of Cf-related Crsmentioning
confidence: 99%
“…66 However, recently published data from a multicenter, double-blind, randomized controlled trial found that sinonasal inhalation with hypertonic saline (NaCl 6.0%) applied with vibrating aerosols was not superior to isotonic (NaCl 0.9%) nasal saline irrigation in patients with CF-related CRS. 64 Additionally, hypertonic saline (6 to 7%) is often associated with an increase of adverse reactions due to its irritating properties on sinonasal mucosa, which provokes cough and airway obstruction. 62,67 As such, use of hypertonic saline may be less efficacious due to a lack of tangible evidence and any previously perceived benefits may be limited by poor patient compliance secondary to its irritating effects.…”
Section: Medical Management Of Cf-related Crsmentioning
confidence: 99%
“…As a patient related outcome measure (PROM) it assesses quality of life in patients with CRS. Previously, it was applied in a series of conservative interventional trials, among these some performed in our CF center . Rhinoscopic examination can detect sinonasal irregularities such as NP, hypertrophic inflamed mucosa, mucus and crusts, which could cause subjective and objective symptoms, for example, by obstruction impairing sleep and the UAW climatic function.…”
Section: Introductionmentioning
confidence: 99%
“…In their RCT, which was done in the non‐immediate postoperative period, Mainz et al demonstrated a positive effect of dornase in the treatment of CRS in CF, when compared with isotonic saline, on sinus symptoms, by significant improvements in overall SNOT‐20 scores ( p = 0.017) . In 2016, Mainz et al compared isotonic saline vs hypertonic saline in an RCT in CF sinusitis and demonstrated no difference between them, concluding that dornase alfa appeared to be more effective . Improvement in sinonasal symptoms was also demonstrated in 2 low‐level evidence studies, also in non‐immediate postoperative period .…”
Section: Discussionmentioning
confidence: 99%